Genotyping of Pseudomonas aeuroginosa Isolated form Different Sources Using Random Amplified Polymorphic DNA –PCR Technique - Shammari, Ahmed Abdulhaleem Al (International Journal of Scientific Research in Biological Sciences, 2024)
Pseudomonas aeruginosa is a human pathogen that takes advantage of patients with weak immune systems, causing severe acute and chronic diseases. Its ability to create antibiotic-resistant biofilms explains its significant persistence in clinical settings. We collected a maximum of 25 clinical and ecological samples from the general hospitals located within the city of Al-Hilla to characterize the prevalent strains of P. aeruginosa among patients. We isolated and identified Pseudomonas aeruginosa using the culture technique on cetrimide agar at a temperature of 42 °C. A random amplified polymorphic DNA (RAPD) primer named opY-10 was used to observe a total of 6 DNA fragments with sizes ranging from 100 to 1500bp. We commonly detected 13 amplified polymorphic fragments among the 8 isolates of P. aeruginosa from various sources. The use of different primers resulted in distinct genetic profiles. The results indicate that RAPD-PCR analysis is an effective genetic screening technique for identifying genetic variations among pseudomonas aeuroginosa isolates.